A cross-sectional study to determine the energy density and nutritional quality of primary-school children's lunchboxes. Issue 6 (23rd April 2020) - Sutherland, Rachel; Nathan, Nicole; Brown, Alison; Yoong, Serene; Reynolds, Renee; Walton, Alison; Janssen, Lisa; Desmet, Clare; Lecathelinais, Christophe; Gillham, Karen; Herrmann, Vanessa; Wolfenden, Luke
Abstract: Objective: The present study describes the energy content of primary-school children's lunchboxes and the proportion of lunchbox foods considered discretionary. Subgroup analyses by sex, socio-economic status, age and weight status were undertaken. Design: A cross-sectional study was conducted. Mean kilojoule content, number of items and categorisation of foods and drinks in lunchboxes as 'everyday' (healthy) or discretionary (sometimes) foods were assessed via a valid and reliable lunchbox observational audit. Setting: Twelve Catholic primary schools (Kindergarten–Grade 6) located in the Hunter region of New South Wales, Australia. Participants: Kindergarten to Grade 6 primary-school students. Results: In total, 2143 children (57 %) had parental consent to have their lunchboxes observed. School lunchboxes contained a mean of 2748 kJ, of which 61·2 % of energy was from foods consistent with the Australian Dietary Guidelines and 38·8 % of energy was discretionary foods. The proportion of lunchboxes containing only healthy foods was 12 %. Children in Kindergarten–Grade 2 packed more servings of 'everyday' foods (3·32 v . 2·98, P < 0·01) compared with children in Grades 3–6. Children in Grades 3–6 had a higher percentage of energy from discretionary foods (39·1 v . 33·8 %, P < 0·01) compared with children in Kindergarten–Grade 2 and children from the most socio-economically disadvantaged areas had significantly higher total kilojoules in the school lunchbox compared with the least disadvantaged students (2842 v . 2544 kJ, P = 0·03). Conclusions: Foods packed within school lunchboxes may contribute to energy imbalance. The development of school policies and population-based strategies to support parents overcome barriers to packing healthy lunchboxes are warranted.